- #1

- 18

- 0

This is what I'm doing for each one:

ln(-e)= e^ln(-e)

(-1)^i= e^(i)(ln(-1))

(2i)^1+i= e^(1+i)ln(2i)

If this is right, where do I go from here?

- Thread starter ilikephysics
- Start date

- #1

- 18

- 0

This is what I'm doing for each one:

ln(-e)= e^ln(-e)

(-1)^i= e^(i)(ln(-1))

(2i)^1+i= e^(1+i)ln(2i)

If this is right, where do I go from here?

- #2

HallsofIvy

Science Advisor

Homework Helper

- 41,833

- 961

One reason the problem specifically says "in rectangular form" is that you will want to convert to "polar form" to do the calculations- then convert back.

If you write a complex number z= x+iy in "polar form" as

r e

In particular, -e= e e

For (-1)

- Last Post

- Replies
- 1

- Views
- 2K

- Last Post

- Replies
- 5

- Views
- 965

- Last Post

- Replies
- 1

- Views
- 1K

- Last Post

- Replies
- 3

- Views
- 1K

- Last Post

- Replies
- 4

- Views
- 1K

- Last Post

- Replies
- 2

- Views
- 939

- Last Post

- Replies
- 15

- Views
- 5K

- Last Post

- Replies
- 6

- Views
- 1K

- Replies
- 2

- Views
- 1K

- Replies
- 5

- Views
- 8K